2021
DOI: 10.1161/circinterventions.120.010007
|View full text |Cite
|
Sign up to set email alerts
|

Patient Selection and Clinical Outcomes in the STOPDAPT-2 Trial

Abstract: Background: We sought to evaluate the impact of patient selection for the STOPDAPT-2 trial (Short and Optimal Duration of Dual Antiplatelet Therapy After Everolimus-Eluting Cobalt-Chromium Stent-2) on clinical outcomes in a registry from a single center that participated in the STOPDAPT-2 trial. Methods: Among 2190 consecutive patients who underwent percutaneous coronary intervention using stent in Kokura Memorial Hospital during the enrollment period o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…However, thrombotic risk of patients with ACS is known to attenuate over time . Moreover, the prevalence of patients with high bleeding risk is much higher in real clinical practice than in clinical trials . Therefore, de-escalation of antithrombotic therapy in parallel with time-dependent attenuation of thrombotic risk might be a reasonable approach in patients with ACS.…”
Section: Discussionmentioning
confidence: 99%
“…However, thrombotic risk of patients with ACS is known to attenuate over time . Moreover, the prevalence of patients with high bleeding risk is much higher in real clinical practice than in clinical trials . Therefore, de-escalation of antithrombotic therapy in parallel with time-dependent attenuation of thrombotic risk might be a reasonable approach in patients with ACS.…”
Section: Discussionmentioning
confidence: 99%
“…14 Furthermore, a considerable number of patients eligible for the study were not enrolled because of physician’s choice or patient refusal despite the all-comer study design, who were reported to have higher risk for both cardiovascular and bleeding event than those actually enrolled. 16 Therefore, the favorable results of 1-month DAPT in patients with complex PCI should be regarded as hypothesis-generating, and the safety and efficacy of clopidogrel monotherapy after very short DAPT in patients with complex PCI should be confirmed in larger studies. Second, we set 90 days as the time period for screening the staged PCI.…”
Section: Discussionmentioning
confidence: 99%
“…DAPT continuation at 12 months in the 2015-2017 PENDULUM (Platelet Reactivity in Patients with Drug Eluting Stent and Balancing Risk of Bleeding and Ischemic Event) study of PCI cases (6,267 patients) was 70-80% [ 13 ]. In addition, the 12-month DAPT continuation rate for patients who met the enrollment criteria in the STOPDAPT-2 trial but were not enrolled (2016-2017) was 73% [ 14 ]. Thus, in DAPT, physician prescribing bias in clinical practice tends to be longer-term than guideline recommendations.…”
Section: Reviewmentioning
confidence: 99%